The influence of regional culture on post-sixteen educational choices and directions from school in Lincolnshire: a qualitative study - Atkin, Christopher (2002)
This thesis investigates the influence of regional culture on young people's decision making when considering post-sixteen educational choices and directions from school. The data is provided by life story interviews with young people - aged eighteen to twenty years, 'born and bred' in Lincolnshire - who have followed four pathways from compulsory education. Within the context of Lincolnshire the influence of rurality is a major element of regional culture and figures in much of the discussion and analysis.